Sarcoidosis Mimicking Skull Base Meningioma - Chaves, Jennyfer Paulla Galdino; Mattozo, Carlos Alberto; Maeda, Adriano Keijiro; Filla, Luciane; Piva, Aline Kelly de Cezaro; Suzuki, Thiago; Silva, Larissa Luvison Gomes da; Francisco, Alexandre Novicki (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Sarcoidosis is a systemic disease characterized by granulomatous inflammation. Pulmonary and lymphatic granulomatous involvement are common. We present a rare case report of involvement of the central nervous system affecting the ocular region and mimicking optic nerve sheath meningioma. We report the case of a 79-year-old female patient with progressive visual impairment with an evolution of 4 years. A magnetic resonance imaging scan of the cranium with gadolinium and intense homogeneous contrast enhancement revealed an expansive lesion in the right optic nerve, at the height of the optic canal. The patient was submitted to the neurosurgical approach with lesion biopsy, which showed sarcoidosis of the central nervous system. Due to the rarity of central nervous system involvement, the diagnosis of this pathology may unfortunately be postponed. The present article aims to elucidate this pathology as a differential diagnosis of retro-orbital tumors.
Keywords: sarcoidosis; ocular sarcoidosis